2010
DOI: 10.1002/ppap.201000049
|View full text |Cite
|
Sign up to set email alerts
|

Main Species and Physicochemical Processes in Cold Atmospheric‐pressure He + O2 Plasmas

Abstract: The main species and chemical processes in low‐temperature atmospheric‐pressure He + O2 plasmas are identified using a comprehensive global model. The simulation results highlight the significance of Penning processes at low oxygen concentration, and the increasingly important role of electron attachment as the oxygen concentration increases. With increasing the oxygen concentration, the electron energy dissipation shifts from elastic collisions with He to dissociative excitation and attachment of O2 molecules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
152
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 171 publications
(165 citation statements)
references
References 77 publications
11
152
0
Order By: Relevance
“…16 where the main species and dominant reactions in HeþO 2 plasmas were selected out of 250þ reactions. In that study 3 regimes were identified based on the oxygen concentration in the background gas.…”
Section: Description Of the Modelmentioning
confidence: 99%
See 4 more Smart Citations
“…16 where the main species and dominant reactions in HeþO 2 plasmas were selected out of 250þ reactions. In that study 3 regimes were identified based on the oxygen concentration in the background gas.…”
Section: Description Of the Modelmentioning
confidence: 99%
“…16 Besides the main 55 reactions identified in Refs. 16 and 5 additional reactions that were neglected due to the overestimation of the radial flux in the previous study 16 have been incorporated. The paper is organized as follows.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations